PRACTICAL IMPORTANCE OF DEFINING THE AMOUNT OF RETICULOCYTES IN PERIPHERAL BLOOD OF ACTIVE BLOOD DONORS - Derpak, J.J. (World of Medicine and Biology, 2016)
The article cover data concerning methods of defmitmg the amount of reticulocytes The results of own research are given. Differential and diagnostic and prognostic role of estimating the amount of reticulocytes are discussed.
Keywords: blood donors; reticulocytes; peripheral blood; research